Pengaruh Kualitas Pelayanan Pengurus Terhadap Keberhasilan Koperasi Sehati Makmur Abadi Kabupaten Banyuasin - Abrar; Riri Hanifah (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of the service quality of the management on the success of the Sehati Makmur Abadi Cooperative in Banyuasin Regency. The data use disprimary data with the data collection method using a questionnaire. The sampling technique use dispurposive sampling with the number of sample stakenis 20 percent of the population as many as 36 respondents. The analytical method used is Simple Regression Analysis. The results showed that the service quality of the management had a positive relationship to the success of the cooperative. Based on the results of the statistical t test, it was found that the service quality of the management had a significant effect on the success of the cooperative. The value of the coefficient of determination (R2) shows the result of 0.70, which means that the success of the Sehati Makmur Abadi Banyuasin Cooperative can be explained by 70% by the independent variable, namely the quality of management services. While there maining 30% is influenced by other factors outside the model.